REVIEW OF TRENDS, APPROACHES AND PERSPECTIVE PRACTICES OF STEM-EDUCATION FOR TRAINING CENTER OPENING (Journal of Information Technologies in Education (ITE), 2017)
STEM is one of the most current educational trends, it provides young people training according to information society in the science, technology, engineering and mathematics. The leading ideas are interdisciplinary education by solving real practical problems, project work and cooperation. The state of STEM-education in the world and Ukraine is analyzed. Particular attention is paid robotics that enables to develop programming skills and design, and it is the integrator of all components of STEM. The range of services in robotics, constructors for learning is considered. The experience of STEM-center of Kherson State University is presented.
Keywords: robotics; Educational robotics; STEM; ICT; LLL